2002
DOI: 10.1002/ejsp.139
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for changing power positions and power distances: a social value orientations approach

Abstract: Participants were asked to put themselves in the position of one of three persons who differed in the amount of power they had in a small work unit. Subsequently, they could allocate points on a power scale to themselves and the two others, and thus, change the power positions and the power distances between the positions. The least powerful individuals had the strongest tendency to increase their power. They wanted to reduce the power distance to the person in the higher position more than the power distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…This corroborates existing research (Poppe, 2003;Van Dijke & Poppe, 2003, 2004) by means of a new power operationalization. More importantly, we showed that people attempt to change the power difference to their advantage by decreasing their dependence on others' power, to increase their personal power.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This corroborates existing research (Poppe, 2003;Van Dijke & Poppe, 2003, 2004) by means of a new power operationalization. More importantly, we showed that people attempt to change the power difference to their advantage by decreasing their dependence on others' power, to increase their personal power.…”
Section: Discussionsupporting
confidence: 91%
“…Results of Van Dijke and Poppe (2004; see also Poppe, 2003;Van Dijke & Poppe, 2003) support the notions of Tjosvold et al (1991) and Kotter (1978Kotter ( , 1985, that people sometimes increase their social power when it is instrumental for an increase of their personal power. In this study, like in the studies by Wilke (1992, 1993) and Mulder and his colleagues (Mulder, Veen, Hartsuiker, & Westerduin, 1971;Mulder, Veen, Hijzen, & Jansen, 1973;Mulder, Veen, Rodenburg, Frenken, & Tielens, 1973), participants worked together with others in a hierarchical group.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…As has been shown in number of studies (Poppe, 2003;Van Dijke & Poppe, 2004), people try to accumulate more power in relation to others on the same hierarchical level, also as a means to distinguish themselves from others. However, this tendency decreases if power differences in groups are recognized in terms of hierarchical differences.…”
Section: A Model Of Expertise In Teamsmentioning
confidence: 96%